Sending the message: specialized RNA export mechanisms in trypanosomes. Issue 10 (October 2022) - Obado, Samson O.; Rout, Michael P.; Field, Mark C.
Abstract : Export of RNA from the nucleus is essential for all eukaryotic cells and has emerged as a major step in the control of gene expression. mRNA molecules are required to complete a complex series of processing events and pass a quality control system to protect the cytoplasm from the translation of aberrant proteins. Many of these events are highly conserved across eukaryotes, reflecting their ancient origin, but significant deviation from a canonical pathway as described from animals and fungi has emerged in the trypanosomatids. With significant implications for the mechanisms that control gene expression and hence differentiation, responses to altered environments and fitness as a parasite, these deviations may also reveal additional, previously unsuspected, mRNA export pathways. Highlights: mRNA export is a highly complex process at the core of gene expression controlling mRNA abundance. Steps include maturation, quality control ensuring that mRNAs are correctly coding, and the export process itself. Trypanosomes have distinct mechanisms for producing mRNA which sets them apart from animals and fungi. These include trans -splicing, absence of introns within open reading frames and polycistronic transcription. These require distinct processes to produce mature mRNAs, which are near identical in structure to higher eukaryotes. We describe how distinct mechanisms for mRNA processing have resulted in changes to mRNA export mechanisms, encompassing nuclear pore complex composition and organization, mRNA maturation, and quality control mechanisms.